ListeningTime; participatory development of a web-based preparatory communication tool for elderly cancer patients and their healthcare providers - Noordman, Janneke (Internet Interv, 2017)
OBJECTIVE: This paper outlines the participatory development process of a web-based preparatory communication tool for elderly cancer patients and their oncological healthcare providers (HCPs). This tool aims to support them to (better) prepare their encounters. An overarching aim of the project is to develop the tool in a participatory way to increase uptake and use. METHODS: Scrum, a participatory framework originated from software development, was applied to develop the tool. Using constant feedback loops, elderly (former) cancer patients, oncological HCPs and their representatives were, as end-users, involved. RESULTS: During six ‘sprints’, the communication tool ‘ListeningTime’ was developed with input from end-users. The use of scrum in developing an innovative tool was challenging in this context, because of time constraints of seriously-ill patients and busy HCPs and the co-creation involving non-profit scientific researchers and a for-profit development company. CONCLUSIONS: The collaboration with end-users facilitated the development process of ListeningTime. Early involvement of end-users and flexibility in terms of planning and setup appear to be preconditions for creating a bottom-up inspired development procedure. Several challenges emerged from using scrum as participatory framework. Nevertheless, the ‘pressure cooking situation’, using scrum, resulted in a quick development process and a product ready for implementation.